Lombok Pumice for Adsorption of Fe2+ Metal Ions Using Activation Temperature Variations - Sinta Devi Hariyanti; Susi Rahayu; Siti Alaa’; Dian Wijaya Kurniawidi (Jurnal Biologi Tropis, 2023)
Fe is a heavy metal that is often found in water. If the level exceeds the maximum limit and is continuously consumed, it will cause various kinds of diseases so that a method is needed that can reduce the level of heavy metal Fe2+. In this study, Fe2+ metal ion adsorption was carried out using pumice which aims to determine the characteristics of pumice which include surface area, density and porosity, adsorption ability, and determine the contact time required to absorb Fe2+ metal ions. The adsorption method used is the batch method, with activation treatment for each adsorbent. Activation is done by heating at a temperature variation of 250o, 400o, and 550oC. The results showed that the highest adsorption capacity of pumice was activated pumice powder at a temperature of 550oC with a characteristic surface area of ​​8.196 m2/g, porosity 12.722% and density 2.374 gr/cm3 and the best contact time was at 60 minutes with absorption efficiency 86.4%